A REVIEW FOR MEDICAL AND DENTAL PROFESSIONALS CONCERNING THE NEW MONKEY POX WARNING - Dr Simrat Bhullar; Dr Harnoor Singh; Dr Reshma Dodwad; Dr Navpreet Singh; Dr Vithal Kumar Malleshi Betigeri; Dr Harnoor Singh Sandhu; Dr Avineet Kaur (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
MPXV, or monkey pox virus, is a associated with Poxviridae family and the Ortho poxvirus genus. Only two different species of wild animals— just like a a rope squirrel located in the Democratic Republic of the Congo and a sooty mangabey in Ivory Coast—have had a virus isolated from them. Protection against monkey pox infection after receiving the smallpox vaccine was calculated to be around 85%. Since smallpox was finally eradicated in 1980, widespread vaccination campaigns have tapered down. That opened the door for monkey pox to be considered as a bioterror threat.